Penyegaran Kader ‘Aisyiyah tentang Diabetes Mellitus melalui Edukasi Kesehatan - Rahayu, Sri; Kristinawati, Beti; Maliya, Arina; Oktaviana, Wita; Angga Pribadi, Dimas Ria (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Refreshing ‘Aisyiyah cadres about diabetes mellitus through health education is an important effort to improve cadres’ understanding in preventing and managing diabetes mellitus. The purpose of this community service is to provide refreshment to ‘Aisyiyah cadres through health education to improve knowledge about diabetes mellitus. In this activity, ‘Aisyiyah cadres are given the latest knowledge about risk factors, normal blood sugar values, symptoms, and control of diabetes, as well as preventive measures that can be implemented in daily life. Participants are evaluated by giving questions using a questionnaire during the pre and post tests. The results showed an increase in participant knowledge from 90.24% to 92.6% after health education was carried out. Through this activity, it is hoped that ‘Aisyiyah cadres can play an active role in preventing an increase in the incidence of diabetes mellitus in the community